2014
DOI: 10.1037/npe0000025
|View full text |Cite
|
Sign up to set email alerts
|

Advertising memory: The power of mirror neurons.

Abstract: International audienceAs part of the insights of neuroscience available for the study of advertising, the concept of mirror neurons provides opportunities for new research. Mirror neurons are a particular class of visuomotor neurons in the brain that show activity both when an individual performs an action and when he observes another individual performing the same action. According to researchers in cognitive neuroscience, mirror neurons are the brain basis for learning by imitation. The observation of 2 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…Specifically, our findings revealed that objects involved in dynamic grasping actions during the encoding phase, in the human-hand condition were recalled more effectively than static objects. This supports and expands upon limited prior research 24 , which has shown that goal-oriented interactions with an object enhance recall and recognition compared to mere observation of a static item. Conversely, Guérard et al (2015) 41 observed immediate retention benefits with objects, but these effects did not persist over longer periods.…”
Section: Action Observation Effects On Subsequent Memorysupporting
confidence: 85%
See 1 more Smart Citation
“…Specifically, our findings revealed that objects involved in dynamic grasping actions during the encoding phase, in the human-hand condition were recalled more effectively than static objects. This supports and expands upon limited prior research 24 , which has shown that goal-oriented interactions with an object enhance recall and recognition compared to mere observation of a static item. Conversely, Guérard et al (2015) 41 observed immediate retention benefits with objects, but these effects did not persist over longer periods.…”
Section: Action Observation Effects On Subsequent Memorysupporting
confidence: 85%
“…Notably, observing goal-oriented actions of others serves as one such influential cue. As demonstrated by Lacoste-Badie and Droulers 24 , the act of witnessing an object as the intended goal of another's actions can enhance recall and recognition of that object. This suggests the presence of an implicit link between memory processes and the phenomenon of goal contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Satın alma açısından ise ayna nöronlar satın alma davranışını taklit etme biçiminde ortaya çıkmaktadır. 10 Marka bağlılığı, ünlülerin marka ikonu hâline gelmesi gibi durumlar ayna nöronlar sayesinde ürün değil de tutum ya da imajı satın almış hissi uyandırmaktadır.…”
Section: Nöropazarlama Ve Beyi̇nunclassified
“…Mirror neurons are a specific type of visuomotor neurons in the brain that display activity when a person performs an action and when they see another person performing a similar movement (Lacoste-Badie & Droulers, 2014). Understanding mirror neurons can help in better explaining consumer behavior (Janiszewski & Wyer, 2014).…”
Section: Introductionmentioning
confidence: 99%